The most common contact lens-related complications: A brief review of the literature - Wojciech Mazurek; Barbara Rękas; Monika Stradczuk; Łukasz Mazurek; Zuzanna Czach; Dominika Bachurska; Mateusz Piętak; Barbara Kruczyk; Joanna Olędzka; Wojciech Kopacz (Kazimierz Wielki University, 2024)
Introducion and purpose Millions of people use contact lenses every day. Their primary and most common use is correcting refractive errors. Despite their beneficial purpose, contact lens use has many complications. It is estimated that 5 to 50% of patients may develop at least a single complication. The state of knowledge Contact lens-related complications are multifactorial. One of the main reasons for contact lens discontinuation is contact lens discomfort. Patients most often report dryness, burning, and irritated eyes. Other disorders can be briefly divided into conjunctival and corneal complications. The most common conjunctival and allergic complication of contact lens use is giant papillary conjunctivitis. Other significant conditions involving the conjunctiva can also be superior limbic keratoconjunctivitis or allergic or toxic conjunctivitis. Corneal complications, on the other hand, seemed to be much more severe. These include superficial punctate keratitis, peripheral corneal ulceration, and contact lens-related keratitis. Also, abrasion can occur due to improper eye hygiene or mechanical damage during lens replacement. It should also be remembered that prolonged use of lenses can lead to hypoxia and corneal edema. Summary This paper briefly outlines the possible complications of contact lens use. It is important to remember that despite their appropriate use, sometimes significant complications can occur. Noteworthy, corneal, or conjunctival complications require discontinuation of the lenses and appropriate treatment.